„Tradycja liturgiczna” w dokumentach i wypowiedziach papieskich dotyczących dyscypliny sprawowania liturgii z 1962 r. po Soborze Watykańskim II - Pietras, Dawid (Człowiek i Społeczeństwo, 2022)
„Liturgical tradition” is a living form that expresses the Apostolic Tradition, which is the unchanging deposit of the Revealed Divine Truths. After the Second Vatican Council, the liturgical tradition that was included in the books of 1962 has been maintained on certain rules. The discipline of celebrating this liturgy changed depending on the attitude of the pope. The possibility of celebrating it has been gradually restored. Eventually, Pope Benedict XVI sanctioned the liturgy as the extraordinary form of the Roman Rite and ensured the general right to celebrate it. Currently – as a result of Pope Francis’s decision – it is emphasized that the liturgy reformed after Vaticanum II is the unique expression legis orandi of the Roman Rite.